2015
DOI: 10.1111/1758-2229.12292
|View full text |Cite
|
Sign up to set email alerts
|

Polychaete burrows harbour distinct microbial communities in oil‐contaminated coastal sediments

Abstract: Previous studies have shown that the bioturbating polychaete Hediste (Nereis) diversicolor can affect the composition of bacterial communities in oil-contaminated sediments, but have not considered diversity specifically within bioturbator burrows or the impact on microbial eukaryotes. We tested the hypothesis that H. diversicolor burrows harbour different eukaryotic and bacterial communities compared with un-bioturbated sediment, and that bioturbation stimulates oil degradation. Oil-contaminated sediment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Several studies have shown that fungi are abundant in marine sediments (Orsi et al, 2013a, b;Xu et al, 2014;Taylor and Cunliffe, 2015). Xu et al (2014) used a similar Q-PCR-based approach to quantify fungi in sediment samples collected from five deep-sea sites in the Pacific Ocean and showed that Fungi-specific 28S rRNA gene copies ranged from 3.5 × 10 6 to 5.2 × 10 7 copies per g wet sediment (Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that fungi are abundant in marine sediments (Orsi et al, 2013a, b;Xu et al, 2014;Taylor and Cunliffe, 2015). Xu et al (2014) used a similar Q-PCR-based approach to quantify fungi in sediment samples collected from five deep-sea sites in the Pacific Ocean and showed that Fungi-specific 28S rRNA gene copies ranged from 3.5 × 10 6 to 5.2 × 10 7 copies per g wet sediment (Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…After 18 h, 1 l seawater samples were removed, filtered through 0.2 µm filters and the filters stored at −80°C. RNA was extracted from the filters as previously described (Taylor and Cunliffe, ) and cDNA generation was performed using the Omniscript RT kit (Qiagen) in accordance with manufacturer's instructions using the reverse primer PROK1492R (Suzuki et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…After 18 h, 1 l seawater samples were removed, filtered through 0.2 mm filters and the filters stored at 2808C. RNA was extracted from the filters as previously described (Taylor and Cunliffe, 2015) and cDNA generation was performed using the Omniscript RT kit (Qiagen) in accordance with manufacturer's instructions using the reverse primer PROK1492R (Suzuki et al 2000). The V4 region of the 16S rRNA gene was amplified by PCR using primers 515F and 806R (Caporaso et al, 2011) from the cDNA and sequenced on an Ion Torrent PGM (Life Technologies) in accordance with manufacturer's instructions.…”
Section: Introductionmentioning
confidence: 99%
“…; Pinto & Bemvenuti ; Rosa & Bemvenuti ; Shimanaga et al . ; Taylor & Cunliffe ). The cylindrical morphology and the trajectory of Permian H. tenuis suggest the displacement of a nematodelike organism within the substrate.…”
Section: Discussionmentioning
confidence: 99%